Household saving motives and socio-demographic factors - Korzeniowska, Anna M.; Ulman, Paweł (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
This research was inspired by broad discussions on the motives for saving. We examine the relationship between the motives for saving and the socio-economic characteristics of households in the eurozone, Croatia, Hungary and Poland, such as: the social type of the household, gender of the reference person (RP), their age, level of education, marital status, taking into account the differences in the value of these households’ financial assets. For this purpose, we used data from the Household Finance and Consumption Survey. The logit model was used to analyse with maximum likelihood estimation the different saving motives and country groups. We also used a Poisson model for a count variable. The results demonstrate that the social type of households is crucial in determining their motives for saving, particularly for child education and leaving an inheritance. Additionally, we identify differences in the number and sets of saving motives between households from countries with both high and low levels of financial assets. In countries where households are less well-off, the motive for saving to purchase residential estate is of greater importance. Moreover, households with more financial assets – mainly from the countries of Western Europe – show more concern about saving for old age and investment.